Perception of parents of children under oncological treatment about behavioral techniques used in pediatric dentistry (Research, Society and Development, 2022)
The objective of this study was to evaluate the perception of parents regarding the techniques used in Pediatric Dentistry for the behavioral management of childhood cancer patients. A study was carried out with those responsible for children with cancer treated at the Dentistry Service of the Support Group for Children with Cancer in Bahia. It is an audiovisual exhibition of the different techniques selected by the researchers and the answers were recorded in two questionnaires, in two moments, in the first being only the videos about the techniques, and in the second with a previous explanation of how they were performed, in addition to the audiovisual exhibition. The results obtained revealed that the parents' perception before the explanation of the techniques presented a statistically significant difference when the interviewee's sex was considered (p